ANALISIS PROFESIONALISME GURU PAI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR UNTUK MEWUJUDKAN PEMBELAJARAN YANG EFEKTIF - Munawir; Hernik Alfia Anjani; Fitrianingsih (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
This study is motivated by the importance of teacher professionalism in responding to the demands of 21st-century learning, particularly at the elementary school/Madrasah Ibtidaiyah level. Teachers are required not only to master pedagogical competencies but also to integrate technology and create effective and meaningful learning environments. This study aims to analyze teacher professionalism in improving the quality of learning to achieve effective learning outcomes. The research method used is qualitative with a library research approach, through the analysis of relevant scientific literature published within the last ten years. Data were collected through documentation techniques, while data analysis employed content analysis, including data reduction, data display, and conclusion drawing. The results show that teacher professionalism plays a significant role in improving the quality of learning, as indicated by teachers’ ability to design instruction, manage classrooms, utilize digital technology, and engage in continuous professional development. In conclusion, enhancing teacher professionalism is a key factor in achieving effective learning. The implications of this study suggest that teachers and educational institutions should continuously improve professional competencies through training, digital literacy, and sustainable development